Strategi Pemanfaatan YouTube sebagai Media Penyiaran Daring untuk Mendukung Kemitraan Program di TVRI Yogyakarta - Galih Arya Anarkhi; Ahmad Muntaha (Universitas Muhammadiyah Kotabumi, 2025)
This research purpose to determine TVRI Yogyakarta's strategy in utilizing broadcast programs via the YouTube social media platform. The research approach used is descriptive qualitative with data collection techniques including in-depth interViews, observation and documentation. Data analysis is based on Henry Jenkins' Media Convergence theory, New Media Theory, and Digital Marketing Theory to understand the transformation of local television into a digital ecosystem. The research results reveal that TVRI Yogyakarta is carrying out media convergence by utilizing YouTube as an alternative distribution media. The strategies used include repackaging television content into digital format, creating exclusive content, optimizing YouTube Search Engine Optimization, consistent content uploading, active interaction with viewers, and using YouTube Analytics. This research provides theoretical contributions through the integration of three main theories (media convergence, new media, and digital marketing) in the context of local television, as well as practical contributions in the form of recommendations for digital strategies for local television so that it continues to exist in the era of media convergence.